(3QSGdI PjH GdhdO GdYGb hGdChdGO GdZGad Yf JZjjQ GdUhQ GdYGUjI YfO GdEfJbGd aj OGQ GdeYGO hQLhY CfaSgG Edi GdEfSaGd HYO GdYdh HeUGMHI GdCVOGOs - (3MeRI Hf Ydj Hf CMeO GdaGQSqj GdMGcej GdOQRj , J (B433 (3g`s
(3ChdgG (B:s
(3HSe GdEdg GdYGde HSQGFQ GdNdb GdaGVM dVejQ ef OdS Ydi Cgd GdMb ef GdhGdO GdMfjf hGdTajb hGdWHjH GdfGUM GdQajb s
(3BNQgG (B:s
(3ceG hUd eG eQJ HUdJg hbWY eG fgjJ Yfg JeJ hGdMeO dehdGfG hMOg hGdTcQ dbGFe GdMb YHOg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B63s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3abg GdePGgH GdCNQis